The Effect of Mother’s Knowledge of Balanced Nutrition and Basic Feeding Pattern on A Nutrirional Status of Toddler 1- 3 Years at Posyandu Dusun Krembangan Kabupaten Jombang - Vina Nabila Rizka Nabila; Choirul Anna Nur Afifah (Healthy-Mu Journal, 2023)
Nutritional status was determined from food intake. Adequate and balanced food intake generate the toddler’s with a good or normal nutrirional status. Mothers were the one who had a main role in providing food to their toddlers. This research aimed to identify the characteristics belong to the mothers of toddlers conducted in the Posyandu Dusun Krembangan, Jombang Regency and to determine the effect of mother's knowledge and feeding patterns on the nutritional status of toddlers (W/A). This research used quantitative method based on a cross sectional approach. The amount of the sample are 32 respondents with age range between 12 to 36 months along with their mothers chosen using purposive sampling method. Mother’s knowledge about nutrition also child feeding pattern are obtained through test and nutrirional status of toddlers were obtained by direct weight measurement. Data were analyzed using Kendall’s-Tau b statistical test. The results showed that there was no influence of mother's knowledge about balanced nutrition with toddler's nutritional status (p>0.05) and there was no effect of feeding ix pattern on toddler's nutritional status (p>0.05). It was suggested that public health should improve their activities related to increase the mother’s knowledge about balanced nutrition, nurients food, and nutririon related to toddler’s health also it’s necessary to conduct further research by developing the instrument and using a comprehensive anthropometric index. Keywords : nutritional status, Nutritional Knowledge, Toddler, Feeding Pattern